Vibrational effects on SrTiO3 Ti 1s absorption spectra studied using first-principles methods - Tinte, Silvia Noemi (2008)
We analyze the vibrational effects on the Ti 1s excited states in cubic SrTiO3 and related pre-edge x-ray absorption fine structure using first-principles methods. Ground-state, total-energy and electron-core hole Bethe-Salpeter calculations are performed for different atomic configurations related to eg-symmetry distortions of SrTiO3. From these, we can obtain normal-mode gradients of the electronic excited-state energy, i.e., of the excited-state Born-Oppenheimer surface. This yields the corresponding electron-phonon coupling coefficients that allow us to predict the spectral broadening induced by those vibrational modes.